2003
DOI: 10.1124/dmd.31.3.326
|View full text |Cite
|
Sign up to set email alerts
|

Tissue mRNA Expression of the Rat UDP-Glucuronosyltransferase Gene Family

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:UDP-Glucuronosyltransferases (UGTs) are phase II biotransformation enzymes that glucuronidate numerous endobiotic and xenobiotic substrates. Glucuronidation increases the water solubility of the substrate and facilitates renal and biliary excretion of the resulting glucuronide conjugate. UGTs have been divided into two gene families, UGT1 and UGT2. Tissue distribution of UGTs has not been thoroughly examined, and such data could provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
164
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(176 citation statements)
references
References 23 publications
10
164
2
Order By: Relevance
“…They also reported that mRNAs of UGT1A2, UGT1A3, and UGT1A7, which showed BCP-NG-producing activity in our study, were mainly present in the digestive tract, and their expressions were very low in the liver. Furthermore, they confirmed that UGT2B1, UGT2B2, UGT2B3, UGT2B6, and UGT2B12 of the UGT 2B subfamily were expressed mainly in the liver [22], in which the total mRNA expression level of UGT2B1, UGT2B3, and UGT2B6, which showed BCP-NG-producing activity in our study, was lower than that of UGT1A1.…”
Section: Liver Microsomal Bcp-ng Activitysupporting
confidence: 66%
See 2 more Smart Citations
“…They also reported that mRNAs of UGT1A2, UGT1A3, and UGT1A7, which showed BCP-NG-producing activity in our study, were mainly present in the digestive tract, and their expressions were very low in the liver. Furthermore, they confirmed that UGT2B1, UGT2B2, UGT2B3, UGT2B6, and UGT2B12 of the UGT 2B subfamily were expressed mainly in the liver [22], in which the total mRNA expression level of UGT2B1, UGT2B3, and UGT2B6, which showed BCP-NG-producing activity in our study, was lower than that of UGT1A1.…”
Section: Liver Microsomal Bcp-ng Activitysupporting
confidence: 66%
“…On the basis of these findings of mRNA expression level [22] and BCP-NG-producing activity, the main UGT isoform responsible for BCP-NG formation in the rat liver may be UGT1A1, and UGT2B1, UGT2B3, and UGT2B6 may be supplementarily involved.…”
Section: Liver Microsomal Bcp-ng Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is the predominant site of expression of many UGT isoforms (Shelby et al, 2003), but extrahepatic sources of UGT activity have been found in other organs such as the kidney, skin, lung and small intestine (Grams et al, 2000;Turgeon et al, 2001) and, in smaller amounts, spleen, thymus, brain and heart (Burchell and Coughtrie, 1989). We have demonstrated that glucuronidated iodothyronines are synthesized and secreted by cardiac fibroblasts, not cardiomyocytes, obtained from neonatal rat heart (van der Heide et al, 2002).…”
Section: Introductionmentioning
confidence: 85%
“…Particularly, the highest concentration of this transporter is found in the liver and intestine [ ], two organs playing a prominent role in xenobiotic detoxiication commonly known as "irst-pass metabolism and clearance". Protein expression of MRP2 is highest in enterocytes of the proximal small intestine, decreasing in direction to the terminal ileum [ ], gradient shared with the expression of phase II metabolizing enzymes such as GST and UGT [9,10], thus suggesting that metabolism and transport processes may act coordinately. In the liver, the major biotransformation organ, MRP2 is abundantly expressed in the bile canalicular membranes of the hepatocyte [11], where it plays a role in bile formation through secretion of endogenous substrates such as glutathione GSH and glutathione conjugates.…”
Section: Multidrug Resistance-associated Protein and Its Role In mentioning
confidence: 99%